The effect of post-sintering annealing induced extrinsic dielectric properties in PZT-PZN ceramics - Naratip Vittayakorn (2018)
Pb[(Zr1/2Ti1/2)0.7(Zn1/3Nb2/3)0.3]O3 (PZT-30PZN) powder was prepared using the columbite precursor method. The phase development of calcined powder precursors was analyzed by X-ray diffraction. Dielectric and ferroelectric properties of the as-sintered and annealed samples were measured and correlated with microstructure. The morphology evolution was determined by a scanning electron microscopy (SEM) technique. The as-sintered ceramic exhibited weak relaxor-ferroelectric behavior, with a relatively low dielectric constant maximum measured at 1 kHz (Km@1 kHz) of 14 000. Annealing resulted in a transition to normal-ferroelectric-like behavior, a shift in the dielectric maximum temperature from 310C to 300C, and a dramatic increase of Km@1 kHz to a maximum value of 25 100 for the longer anneal. After thermal annealing at 900C for 1 week a strong enhancement of remanent polarization (Pr) was observed.